ONLINE TABLE RESERVATION WITH PRE-ORDERING - et. al., Dr.K.Subrahmanyam, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Online Table Reservation System is aweb-based solution for a Restaurant’s Pre-Ordering module; automation and digitalization of table reservation process along with pre-ordering of food and parking spot allocation. This system would allow restaurants to increase the scope of business and save a lot of time with table reservations as previous bookings are open. The system also makes it possible to quickly and easily control an online menu that customers can search and use with only a few clicks to place orders. Recommendations would be based on user activation and specifications. A new user would be recommended of the restaurants available best sellers while a regular would be recommended based on their previous food selections. Their starter and other food selections would also raise recommendations. The table will be reserved along with a parking space on the appropriate time-slot so that users do not face inconvenience. Using this system as a building block, we can develop a smartphone-compactable software application